Five new eyed species of Sinella (Collembola: Entomobryidae) from China, with a key to the eyed species of the genus - Zhang, Feng (Zootaxa, 2013)
Five new eyed species of Sinella from China, respectively with 3, 3, 2, 1, 1 ommatidia on each side, are described here: S. longisensilla sp. nov., S. yui sp. nov., S. pseudobrowni sp. nov., S. sacellum sp. nov. and S. gracilis sp. nov. Clypeal chaetae and chaetae along cephalic groove exhibit differences among these species and could be used to distinguish species in Sinella and Coecobrya. A key to the eyed species of the genus is given.